2015
DOI: 10.1016/j.rbr.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigação da ansiedade, depressão e qualidade de vida em pacientes portadores de osteoartrite no joelho: um estudo comparativo

Abstract: We believe that the treatment of patients with OA should consider the combination of pharmacotherapy, psychotherapy, counseling and family support, in order to achieve a better quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 7 publications
1
15
0
7
Order By: Relevance
“…Leite et al reported that OA patients showed a high frequency of metabolic syndrome and depression, which impact both pain and physical function [ 17 ]. In addition, higher rates of depression and anxiety cause lower quality of life in patients with OA [ 18 ]. Therefore, it is crucial to identify and manage disabilities and pain in patients with OA in routine practice, which will enhance patient quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Leite et al reported that OA patients showed a high frequency of metabolic syndrome and depression, which impact both pain and physical function [ 17 ]. In addition, higher rates of depression and anxiety cause lower quality of life in patients with OA [ 18 ]. Therefore, it is crucial to identify and manage disabilities and pain in patients with OA in routine practice, which will enhance patient quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Atualmente, estima-se que a população acima dos 60 anos seja em torno de 19,6 milhões de habitantes (10,2% da população total) e projeções futuras indicam que, em 2020, o Brasil será o sexto país no mundo em número de idosos, ultrapassando a casa dos 30 milhões de pessoas 20 . Com o aumento de indivíduos idosos, cresce também a ocorrência do número de doenças crônicas associadas ao envelhecimento, como é o caso da OA uma doença que afeta as articulações comprometendo a cartilagem hialina e o osso subcondral 21,22 .…”
Section: Discussionunclassified
“…Immediate postoperative pain impairs mobility and reduces the patient's ability to cooperate with rehabilitation treatment [ 33 ]. When experiencing postoperative pain, the patient's difficulty in activities of daily living, physical dependence and motion restriction of the operated limb increase their anxiety and discouragement, which can be a complicating factor in the rehabilitation process and may also increase the patient's perception of pain [ 34 ]. Alternatively, the use of opioid analgesics for pain control after surgery is recommended; however, a systematic review determined that they are associated with several undesirable side effects, including nausea, vomiting, hypotension, urinary retention, delirium and increased infection rates, which consequently generate an increase in the length of hospital stay and an additional financial cost to the procedure [ 18 ].…”
Section: Discussionmentioning
confidence: 99%